The Effects of Data Transparency Policy Reforms on Emerging Market Sovereign Bond Spreads - Choi, Sangyup (IMF Working Papers; Working Paper ;, 2017)
We find that data transparency policy reforms, reflected in subscriptions to the IMF's Data Standards Initiatives (SDDS and GDDS), reduce the spreads of emerging market sovereign bonds. To overcome endogeneity issues regarding a country's decision to adopt such reforms, we first show that the reform decision is largely independent of its macroeconomic development. By using an event study, we find that subscriptions to the SDDS or GDDS leads to a 15 percent reduction in the spreads one year following such reforms. This finding is robust to various sensitivity tests, including careful consideration of the interdependence among the structural reforms.